2021
DOI: 10.1101/2021.03.12.435017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health explains individual deviations from normative range in cognition-associated brain states

Abstract: Links between cognitive deficits and psychiatric disorders have been studied predominantly at the group level, leaving unique individual characteristics largely unknown. Here, we applied normative modeling to UK Biobank data (N=18,634) and estimated the interplay of large-scale brain networks over time (i.e., dynamic brain state) at the individual level. Abnormality in such brain states was linked to individual variation in mental health. Specifically, brain state measures including fractional occupancy were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(83 reference statements)
1
0
0
Order By: Relevance
“…Another important result revealed that fractional occupancy and mean lifetime of a specific brain state at rest are correlated with psychological distress under long-term stress. This finding is consistent with previous studies showing that the fractional occupancy of brain states at rest can predict overall mental health (66) and mental disorders (42). Specifically, we found that fractional occupancy and mean lifetime of state 10 are negatively correlated with psychological distress under long-term stress, which is characterized by high activation of Visual networks, ECN, and ASN.…”
Section: Discussionsupporting
confidence: 93%
“…Another important result revealed that fractional occupancy and mean lifetime of a specific brain state at rest are correlated with psychological distress under long-term stress. This finding is consistent with previous studies showing that the fractional occupancy of brain states at rest can predict overall mental health (66) and mental disorders (42). Specifically, we found that fractional occupancy and mean lifetime of state 10 are negatively correlated with psychological distress under long-term stress, which is characterized by high activation of Visual networks, ECN, and ASN.…”
Section: Discussionsupporting
confidence: 93%